Ways of Writing : The Practice and Politics of Text-Making in Seventeenth-Century New England - Hall, David D. (Book collections on Project MUSE., 2008)
Ways of Writing is about the making of texts in seventeenth-century New England, whether they were fashioned into printed books or disseminated in handwritten form. David D. Hall explores issues of authority and authenticity, the roles of intermediaries, and the political and social contexts of publication, among other issues.